A wave-based optimization framework for 1D and 2D periodic structures. (May 2020) - Boukadia, R.F.; Deckers, E.; Claeys, C.; Ichchou, M.; Desmet, W.
Highlights: Analytical formulas are derived for derivatives in the WFEM framework. An algorithm using line search and an ellipsoid trust-region method is implemented. Parameter estimation is carried out in a unit cell modeling framework. The vibroacoustic performance of metabeams are optimized using an SQP algorithm. The diffuse field STL of a metapanel is optimized near the acoustic coincidence. Abstract: This paper presents a second order optimization method based on the WFEM framework that enables the optimization of finite 1D periodic structures and 2D infinite ones. While optimization at the unit cell level has been done in previous studies, it did not account for the boundary conditions and excitation on the system, which might have an important influence on its dynamics. The proposed methodology exploits semi-analytical derivatives in an optimization algorithm that combines line search and trust region methods. It is tested and validated in a parameter identification procedure and subsequently used to minimize the mean square velocity of metabeams with clamped free boundary conditions. Finally, it is applied to the optimization of the sound transmission loss of a metapanel in the structural-acoustic coincidence region. The proposed scheme is versatile and can be used in a wide range of applications including, model updating, homogenization, design optimization and possibly damage detection.